Alberta and Northeastern British Columbia : showing oil and gas fields and oil and gas discoveries - Geological Survey of Canada (Cartographer); Pedersen, A. S. (Department of Mines and Technical Surveys Canada, 1964)
This map shows oil and gas fields and pipelines, oil and gas discoveries, oil refineries, natural gas processing plants, First Nations reserves, forest reserves, cities and towns in Alberta and British Columbia in 1964. "Map 1039A (tenth edition)" Scale 1:1,267,200, or 20 miles to 1 inch. Includes index to oil and gas fields in the Edmonton area, and list of oil and gas pipeline companies. Inset: [Regional map of Alberta showing pipelines]. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows oil and gas fields and pipelines, oil and gas discoveries, oil refineries, natural gas processing plants, First Nations reserves, forest reserves, cities and towns.